Probabilistic Mapping of Human Visual Attention from Head Pose Estimation - Veronese, Andrea; Racca, Mattia; Pieters, Roel Stephan; Kyrki, Ville (Frontiers in Robotics and AI, 2017)
Effective interaction between a human and a robot requires the bidirectional perception and interpretation of actions and behaviour. While actions can be identified as a directly observable activity, this might not be sufficient to deduce actions in a scene. For example, orienting our face towards a book might suggest the action toward 'reading'. For a human observer this deduction requires the direction of gaze, the object identified as a book and the intersection between gaze and book. With this in mind, we aim to estimate and map human visual attention as directed to a scene, and assess how this relates to the detection of objects and their related actions. In particular, we consider human head pose as measurement to infer the attention of a human engaged in a task and study which prior knowledge should be included in such a detection system. In a user study, we show the successful detection of attention to objects in a typical office task scenario (i.e., reading, working with a computer, studying an object). Our system requires a single external RGB camera for head pose measurements and a pre-recorded 3D point cloud of the environment.